Oroxin A suppresses colorectal tumor growth by regulating the TRIM24-mediated ferroptosis and TSPO pathway - Chenghai He; Chunyan Weng; Zhichao Lai; Hui Luo; Kexin Chen; Tangliang Li; Weimin Li; Guodong Li (iScience)
Summary: Colorectal cancer (CRC) is a common malignancy, and TRIM24, an E3 ubiquitin ligase, is a potential target for various cancers. This study found high TRIM24 expression in CRC, correlating with poor prognosis and disease progression. Oroxin A (OA) was identified as a TRIM24 inhibitor, promoting its degradation and inhibiting CRC cell proliferation, invasion, and migration in vitro. OA treatment linked to ferroptosis-related protein SLC3A2 and angiogenesis regulator TSPO, modulating the expression of key ferroptosis markers in a TRIM24-dependent manner. OA downregulated TRIM24, affecting TSPO ubiquitination and suppressing angiogenesis. In vivo, OA inhibited CRC tumor growth with minimal toxicity. OA is a potent antitumor agent targeting TRIM24, inducing ferroptosis, and inhibiting angiogenesis.